A New Species of Dendrobium Section Spatulata From Maluku, Indonesia - Metusala, Destario; Saputra, Reza; Trimanto; Nisyawati (Phytotaxa, 2021)
Dendrobium dedeksantosoi, a new species of Dendrobium section Spatulata (Orchidaceae: Epidendroideae) from Maluku Islands, Indonesia, is described and illustrated. The flower of this new species is morphologically most similar to Dendrobium busuangense, but differs in having different shape and size of petals and lip as well as a different length ratio between column and column-foot.